Evaluation Of The Coincidence Of Male Pattern Baldness And Pityrosporum Group Of Fungus In Iran - Javanbakht Arash; Famili Sorour; Amirmajdi Monireh Mokhtari (Indian Journal of Dermatology, 2002)
The aetilogy of male pattern baldness (MPB) is not clearly found yet. The present study has been designed to determine if three is a significant statistical coincidence between MPB and pityrosporm group of fungal infection. This cross-sectional study covers 50 men with the diagnosis of MPB who visited the dermatology clinic of Qaem hospital of Mashhad Medical University as the case group and 43 men with no evidence of MPB as the control group. A questionnaire was filled out for each person of the two groups and mycological sampling was done from three parts of the case group scalp (bald, balding, intact areas) and two parts of the control group scalp (vertex and parietal). All the data were analysed using the software SPSS 10.00 and Chi-square, Pearson Chi-square and Friedman tests. Results showed that there was no difference between different degrees of infection in the intact area (p>0.05). Among the three parts of the case group scalp, bald area had the highest degree of infection (p<0.001). The degree of infection in the bald area of the case group scalp was higher than that of the vertex area of the control group scalp (p<0.001), while there was no difference between the degrees of infection in the intact area of the case group scalp and the parietal area of the control group scalp (p>0.05). This study supports some previous studies that claimed that there might be coincidence between MPB and pityrosporum fungal infection.